Menguji keberadaan structural breaks pada transmisi kebijakan moneter di Indonesia - Imronjana Syapriatama; Intan Kusuma Pratiwi (Journal of Enterprise and Development (JED), 2019)
Purpose — This paper investigates the presence of structural breaks in order to determine the regime shift in case of Indonesia economy.Research method — We use the Bai-Perron (2003) to test the breaks within the period of January 2014 – December 2018 and Structural Vector Autoregression (VAR) to generate the model constructed to analyze the monetary transmission mechanism.Result — The result shows that there are four significant structural breaks while SVAR shows the negative relationship between SBIS and the Output and a negative relationship between PUAS and Inflation